Optimization of Arthrospira platensis Growth by Adding Different Carbon Sources on the Culture Media of Catfish Cultivation Waste and Technical Fertilizer - Nyayu Nurul Husna; Marini Wijayanti; Nuni Gofar (Program Pascasarjana Universitas Sriwijaya, 2022)
Nutrients (C, N, and P) can affect the growth and biochemical content of Arthrospira platensis. Ethanol can be a potential carbon source compared to glucose and acetic acid. Glycerol is also potential as a carbon source for the growth of Arthrospira platensis. This research was carried out from June to July 2021 at the Aquaculture Laboratory and Experimental Pond Laboratory of the Aquaculture Study Program, Sriwijaya University. The research method used Completely Randomized Design (CRD) factorial with 2 factors consisting of the first factor with 3 treatments and the second factor with 2 treatments and 3 replications. The inoculant was cultured in liquid fertilizer technical F/2 media for culture stock as initial inoculum with a density of ± 1.0 g L-ˡ. Parameters observed were the density, the specific growth rate, and water quality. The results showed that M1S3 treatment had the highest density with a value reaching 4.95 g L-1 and the highest specific growth rate of 0,33% per day. ANOVA test result showed that the addition of carbon sources in the culture media of fertilizer and technical waste had a significant effect (P<0.05) on the growth rate of Arthrospira platensis. The water quality parameters of each treatment were suitable for Arthrospira platensis culture.